Assessment of climate suitability with land cover distribution for Amara city by Using remote sensing Techniques - Muslim, Hawazen Hassan; Hashim, Bassim M.; Abdullah, Sundus A. (Iraqi Journal of Physics, 2025)
The current study used satellite data and geographic information systems to detect changes in land use and land cover and also studied climate factors, temperature, and humidity in the city of Amara, which is located in the southeast of Iraq, from 1990 to 2022. The study aimed to calculate the land use land cover (LULC) using satellite images from Landsat 5 TM, Landsat 8 OLI, and Landsat 9 OLI2, also from the Meteorological Service; temperature and humidity data were used to calculate the THI index. Iraq was one of the nations most exposed to the altering climate as a result of global warming and its effects. There was an urgent need to research climate change and land use in Amara city as temperatures rose and the city experienced drought and a shortage of rainfall. The findings showed that the percentage of urban areas increased noticeably from (38.2-69.8) km2, the amount of vegetation increased little, and the barren areas were the highest. Low rainfall in the study area and high temperatures caused by global warming are two major variables affecting public safety. The main factors that affect the comfort of residents are temperature and humidity. The results of the climate suitability study also indicated that November and December are considered the most suitable months for the population, while the hottest and most unpleasant months were from the end of May to the beginning of September.